MORPHOLOGICALLY CONTROLLED SYNTHESIS OF NANOSTRUCTURED ZNO USING EMULSION MEDIUM - Andriani, Amelia
ZnO is the first semiconductor material used as a photoanode on Dye-sensitized solar cells (DSSC). The application of ZnO as a photoanode on DSSC did not produce high efficiency. Thus ZnO was later replaced with TiO2. The main problem of ZnO photoanode-based DSSC is the interaction between the crystal facet of ZnO and dyes. ZnO dissolves to form Zn2+ when adsorbing the dye and aggregation of dye on the surface of ZnO. This condition causes the formation of an insulating layer, which inhibits electrons' injection into the semiconductor. This problem can be overcome by modifying the morphology of ZnO crystals. The morphology of ZnO with the O-terminated facet can minimize ZnO dissolution by dyes and aggregation of dye on the surface of ZnO. A research reported that ZnO nanocrystals with different shapes differ on the efficiency of the ZnO photoanode-based DSSC. Based on this report, the crystal morphology is one factor that can influence the efficiency of DSSC. In this research, we conducted the synthesis of ZnO using a hydrothermal method in the emulsion system. The emulsion system can affect the growth of particles and regulate their size, shape, and morphology. The first step in this research was the synthesis of materials using the stable emulsion of CTAB surfactant. The emulsion preparation was carried out by adding a polar phase solution (water, Zn(Ac)2.2H2O, urea, surfactant) dropwise into a nonpolar phase (toluene, n-butanol) while stirred vigorously for 30 minutes. Synthesis of materials was performed by reacting the stable emulsions using a hydrothermal method at 120 ºC for 24 hours. The obtained particles were then filtered, washed using ethanol, deionized water, and acetone, respectively, dried and calcined at 400 ºC for 4 hours. The calcination products were characterized using FE-SEM, Raman spectroscopy, XRD, N2 physisorption, and UV-Vis DRS. Parameters that varied in this research were the pH of the solution, urea concentration, precursor type, and synthesis duration. The XRD result shows that the synthesized materials correspond to the hexagonal wurtzite ZnO crystal structure with ± 27,18 nm average crystallite size. Based on the analysis using FE-SEM, the synthesized material's morphology is the porous aggregate of nanosheet-like particles with edge thicknesses around in the range of 40–70 nm. The average crystallite and pore size of the ZnO nanosheet tends to increase with the urea concentration. The size and morphology of synthesized particles were controlled by changing the pH of the emulsion system. At high OH- ion concentration, the morphology of synthesized material is rod-like particles with thicknesses in the range of 0,5–1 ?m. In other variations of synthesis, the material's morphology was not much different but has quite different in